Design and off-design analysis of a centrifugal compressor for natural gas - Sandro Kojiro Kurauchi (2012)
Centrifugal is the main compressor type used in process industries and pipelines. This work presents the design of a centrifugal compressor in three steps. The first step is the preliminary design that has an unidimensional treatment and is heavily based on empirical data. Then, using the quasi-ortogonals method, the flow in the meridional plane of the impeller channel is analysed and the blade geometry improved. The last step consists of the compressor flow analysis through Computational Fluid Dynamics (CFD) techniques using a commercial software in order to verify any deficiencies in the methodology applied in the preliminary design.